Teacher communication skills in the strengthening and development of student self-identity - Ibnu Chalis Maulana; Rahmi Winangsih; Ing. Rangga Galura Gumelar (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Teacher interpersonal communication plays a decisive role in shaping student self-identity, particularly in Islamic educational institutions that integrate spiritual values into daily academic life. This descriptive qualitative study investigates how verbal, non-verbal, and empathetic communication modalities employed by teachers at Madrasah Aliyah Darul Ihsan, Kota Serang, contribute to the reinforcement of student self-identity. Data were collected through in-depth semi-structured interviews, participant observation, and documentation, involving six purposively selected informants: the school principal, two teachers, two students, and one parent. Data analysis followed the Miles and Huberman interactive model encompassing data reduction, data display, and conclusion drawing complemented by thematic coding and triangulation to ensure credibility and dependability. The findings reveal four dominant communication models practiced by teachers: (1) dialogic-interpersonal communication that promotes two-way, validating interaction; (2) verbal communication that employs motivational language, positive reinforcement, and empathetic responses; (3) non-verbal communication through supportive gestures, eye contact, smiling, and physical proximity; and (4) modeling communication wherein teachers demonstrate Islamic values through exemplary behavior. These communicative practices directly reinforce students' self-confidence, moral character, and religious identity. The study further identifies that a religiously grounded environment encompassing congregational prayers, Quranic recitation, and mentoring programs amplifies the impact of teacher communication. Findings challenge the conventional assumption that identity formation is solely a function of formal curriculum, arguing instead that a 'communicative mentoring ecosystem' is the primary mechanism of identity reinforcement in madrasah settings.